Patients with Persistent Pain after Breast Cancer Treatment Show Enhanced Alpha Activity in Spontaneous EEG. Issue 12 (19th August 2013) - van den, Emanuel N.; Wilder‐Smith, Oliver H. G.; van, Harry; Vissers, Kris C. P.; van, Clementina M.
Abstract Objective The aim of the present study was to investigate whether patients with persistent pain after breast cancer treatment show an enhanced and slowed dominant alpha activity in their electroencephalogram (EEG) recorded during rest in comparison with patients that also had undergone breast cancer treatment but do not have pain. Methods The spontaneous EEG was recorded during rest and before painful stimulation of the calf and analyzed with spectral analysis (Fast Fourier Transformation). Outcome measures, i.e., alpha indices (center of gravity and overall amplitude), were statistically tested between patients with and without persistent pain. Results In comparison with patients without pain, patients with persistent pain after breast cancer treatment show more alpha activity in their spontaneous EEG observed from parietal‐occipital brain regions. Conclusion Persistent pain after breast cancer treatment affects spontaneous brain activity, which might influence cognitive functioning.